(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
This study was intended to obtain the perception of undergraduate and graduate studies of careers in human movement sciences, about teaching, learning and evaluation during the COVID-19 pandemic related to the SARS-CoV-2 virus. A total of 23 students (12 degrees and 11 graduate students) aged between the ages of 19 and 45 participated voluntarily in this study. In order to obtain informed consent of participation, the student was contacted by different virtual means such as social networks. Once the sample was obtained to participate in the investigation, it was proceeded to send by email due consent and the semi-structured interview to be completed by the participants. This interview was designed by the principal investigator and analyzed at the discretion of pedagogy experts. Once the answers were obtained, they were systematized using clusters according to thematic similarity for analysis. The results showed that students perceive more meaningful learning when they are present in the classroom. In addition, they rescue that remote presence facilitates greater use of time and resource and rescue their relevance in courses with a high theoretical component. In addition, they consider that evaluations should focus on the assignment of investigative practices without memoristic testing. Based on the results, it is concluded that in view of the eventuality of the COVID-19 pandemic, the student considers that the methodology of remote presence can be a potential option for the development of theoretical component and use the hours of face-to-face contact for the development of practices that allow him to experience and implement his learning.